Case Report: The first case of successful pregnancy and live birth following laparoscopic resection of adenomyosis under real-time intraoperative ultrasound elastography guidance - Ota, Yoshiaki; Ota, Kuniaki; Takahashi, Toshifumi; Horikawa, Naoki; Kuroda, Ryosuke; Okamoto, Hana; Tanaka, Yu; Kusumoto, Tomoyuki; Oda, Takashi; Matsuyama, Takehiko; Miyake, Takahito; Honda, Tetsuro; et al. (Frontiers in Medicine, 2024)
Objective Adenomyosis-related infertility is increasingly being diagnosed, and surgical intervention has been suggested to improve fertility. Elastography, a noninvasive ultrasound technique, is promising for diagnosing and guiding the resection of adenomyosis. This report presents the first case of successful delivery after twin pregnancies achieved with IVF following intraoperative elastography-guided laparoscopic adenomyomectomy. Case report A 35-year-old Japanese woman with uterine adenomyosis received a gonadotropin analog before surgery. Preoperative MRI revealed a 5.0 × 7.0 cm adenomyoma, leading to scheduled laparoscopic adenomyomectomy with intraoperative elastography. During surgery, elastography ensured the complete resection of the adenomyotic tissue while preserving the endometrium. Postoperative MRI confirmed the absence of residual adenomyosis. The patient underwent in vitro fertilization and embryo transfer, leading to a successful twin pregnancy after double blastocyst transfer. Despite a stable perinatal course, she required hospitalization to prevent preterm labor. At 32 weeks, an elective cesarean section delivered healthy twins. The intra- and post-operation was uncomplicated, and the patient and infants had an optimal health. Conclusion This is the first reported case of a twin pregnancy resulting from vitrified-warmed embryo transfer after elastography-guided laparoscopic adenomyomectomy, culminating in a successful delivery via cesarean section. This technique allows precise resection and mitigates the risks of uterine rupture and placenta accreta spectrum disorders. Although promising, further studies are required to validate the safety and efficacy of this innovative surgical approach.